2019
DOI: 10.1101/535013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuropathy-related mutations alter the membrane binding properties of the human myelin protein P0 cytoplasmic tail

Abstract: 1 Schwann cells myelinate selected axons in the peripheral nervous system (PNS) and contribute to fast 2 saltatory conduction via the formation of compact myelin, in which water is excluded from between tightly 3 adhered lipid bilayers. Peripheral neuropathies, such as Charcot-Marie-Tooth disease (CMT) and Dejerine-4

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 60 publications
(114 reference statements)
1
28
0
Order By: Relevance
“…Systematic biophysical characterizations using simplified lipid compositions have been performed on P0ct, which revealed that P0ct alone is an IDP in solution but folds upon irreversible association with negatively charged detergent micelles and lipid vesicles [ 58 , 59 , 60 , 61 ]. P0ct embeds deep into the lipid structure and affects the mechanical and thermodynamic properties of its surroundings [ 41 , 44 ]. This association in simplified model systems is influenced by ionic strength and the presence of Ca 2+ [ 62 ], and it generally resembles the behavior of MBP under similar conditions, which involves a large gain of structural content [ 41 , 58 , 59 , 60 , 61 , 63 ].…”
Section: The Molecular Structure Of P0mentioning
confidence: 99%
See 3 more Smart Citations
“…Systematic biophysical characterizations using simplified lipid compositions have been performed on P0ct, which revealed that P0ct alone is an IDP in solution but folds upon irreversible association with negatively charged detergent micelles and lipid vesicles [ 58 , 59 , 60 , 61 ]. P0ct embeds deep into the lipid structure and affects the mechanical and thermodynamic properties of its surroundings [ 41 , 44 ]. This association in simplified model systems is influenced by ionic strength and the presence of Ca 2+ [ 62 ], and it generally resembles the behavior of MBP under similar conditions, which involves a large gain of structural content [ 41 , 58 , 59 , 60 , 61 , 63 ].…”
Section: The Molecular Structure Of P0mentioning
confidence: 99%
“…Due to available structural information, the Ig-like domain and its role in defining the spacing of the IPL have been the focus of several studies. In contrast to the literature published on the Ig-like domain and IPL formation, studies focusing specifically on the structure-function relationships of P0ct account for a small fraction of experimental data available for P0 [ 41 , 44 , 58 , 59 , 60 , 61 ]. MBP and P0ct share similar physicochemical characteristics, which potentially confers P0ct with MBP-like functions.…”
Section: P0 Is the Executive Pns Membrane Stackermentioning
confidence: 99%
See 2 more Smart Citations
“…However, these structures are very close to the myelin membrane and therefore are likely to be folded, as experimentally shown for the loops of proteolipid protein [23]. Another example is the C-terminal extension of P0 (P0ct), which is disordered in the absence of lipids, but not under membrane-like conditions [19,[51][52][53][54]. In vivo, the lipidated P0ct directly follows the transmembrane helix of P0 in the cytoplasmic compartment of PNS compact myelin, permanently anchoring it to the phospholipid membrane, whereby it folds and is thus unlikely to function as a canonical IDP [55].…”
Section: General Attributes Of Myelin-specific Proteinsmentioning
confidence: 87%